Java Memory Management a comprehensive guide to garbage collection and JVM tuning - Van Putten, Maaike; Kennedy, Seán (Packt Publishing, Limited, 2022)
Improve application performance by tuning, monitoring and profiling both the garbage collector and JVM Key Features Understand the different parts of Java memory and the various garbage collectors so you can select your preferred one Explore how memory management can help to effectively improve performance Learn how to spot and avoid memory leaks to enhance application performance Book Description Understanding how Java organizes memory is important for every Java professional, but this particular topic is a common knowledge gap for many software professionals. Having in-depth knowledge of memory functioning and management is incredibly useful in writing and analyzing code, as well as debugging memory problems. In fact, it can be just the knowledge you need to level up your skills and career. In this book, you'll start by working through the basics of Java memory. After that, you'll dive into the different segments individually.
1st edition - Cover
Includes index. - Description based upon print version of record
Keywords: Speicherverwaltung; Java -- Programmiersprache; Java (Computer program language); Memory management (Computer science)